Supra-subduction zone magmatism of the Kocali ophiolite, SE Turkey - Beyarslan, Melahat (Pergamon-Elsevier Science Ltd, 2017)
The Late Cretaceous Kocali ophiolite is an important element within the southeastern Anatolian ophiolite belt and contains all components of a complete ophiolite, including mantle peridotites (harzburgites, and subordinate dunite) gabbros, sheeted dyke complexes, lower volcanic unit (pillowed basalts), and upper volcanic unit (andesite and andesitic pyroclastics) plagiogranite and ultramafic rocks intruded into the gabbros. All components of the Kogan ophiolites show strong suprasubduction-zone affinities, from harzburgitic mantle to basaltic lavas. The radiolarian faunas and geochronological data indicate that there are two different volcanic units: Tarasa volcanics and volcanics of the Kocali ophiolite. While the Tarasa volcanics are of Carnian to Rhaetian age, the Kocali ophiolite is of the Late Cretaceous age. The geochemical features indicate an E-MORB source for the Tarasa volcanics, and a forearc source for the Kocali ophiolite. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Forearc; Supra-subduction; Ophiolite; Kocali; Adiyaman; Turkey